The Effect of Brand Performance, Consumer Testimonials, and Brand Ambassadors on Customer Loyalty - Naurah Dhia; Desy Widiasary Simangunsong; Muhammad Rakha Al Ghaniy; La Mani (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The sportswear industry faces intense competition, requiring brands to build strong customer loyalty through effective digital marketing strategies. This study aims to analyze the influence of brand performance, consumer testimonials, and brand ambassadors on customer loyalty for the Puma sportswear brand, specifically through its Instagram campaigns. Data were collected through an online survey of 398 followers of the Puma Indonesia Instagram account, using a structured questionnaire measured on a five-point Likert scale. The analysis employed Structural Equation Modeling–Partial Least Squares to test the relationships between variables. The findings reveal that brand performance, consumer testimonials, and brand ambassadors each have a significant positive impact on customer loyalty. High-quality products and innovative designs enhance satisfaction, authentic testimonials shared on Instagram build trust, and credible ambassadors foster emotional connections with consumers. These strategies collectively strengthen loyalty in a competitive market. The study concludes that sportswear brands should optimize product quality, leverage user-generated testimonials, and select ambassadors aligned with their audience to enhance customer retention on digital platforms like Instagram. The implications of these findings suggest that sportswear brands should maintain and optimize these strategies to retain customer loyalty amid intense market competition.